2002
DOI: 10.7863/jum.2002.21.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Enhances Early Healing of Medial Collateral Ligament Injuries in Rats

Abstract: Low-intensity pulsed ultrasound exposure is effective for enhancing the early healing of medial collateral ligament injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…Enhanced bone healing in tibial [10], radial [11], scaphoid [38] and mandibular [39] fractures has been observed. Studies carried out on animal models of ligament, tendon and cartilage injury demonstrated the beneficial effects of US stimulation in wound repair of tissues other than bone [40][41][42]. In US exposed repaired Achilles tendons, an increased order in the extracellular matrix network and collagen fibres distribution has been found [43].…”
Section: Discussionmentioning
confidence: 96%
“…Enhanced bone healing in tibial [10], radial [11], scaphoid [38] and mandibular [39] fractures has been observed. Studies carried out on animal models of ligament, tendon and cartilage injury demonstrated the beneficial effects of US stimulation in wound repair of tissues other than bone [40][41][42]. In US exposed repaired Achilles tendons, an increased order in the extracellular matrix network and collagen fibres distribution has been found [43].…”
Section: Discussionmentioning
confidence: 96%
“…61,73 Low-intensity vibro-acoustic stimulation, typically delivered in the form of pulsed US of <50 mW/cm 2 , accelerates the healing of neural tissue, 82 cartilage, 54,55 tendon, and bone. 13,14,21,23,31,33,50,57,65,72,75,85 Pulsed US treatment also increases the rate of bone formation in distractions. 11,24,25,68,79 Exposure to low-intensity pulsed US (1.5 MHz, 30 mW/cm 2 ) for 20 min a day resulted in a 36% acceleration in the healing rate of distal radial fractures 44 and a reduction in the healing time of tibia fractures from 154 to 96 days.…”
Section: Introductionmentioning
confidence: 94%
“…Low intensity vibro-acoustic stimulation, typically delivered in the form of "diagnostic-intensity-level" pulsed ultrasound (US) of less than 50 mW/cm 2 , accelerates the healing of neural tissue, cartilage, tendon, and bone. 3,6,12,29,34,37,40 Pulsed US treatment also increases the rate of bone formation in distractions. 7 Numerous clinical studies have documented the healing of nonunions and significant reductions in the healing time of fractures that were treated with pulsed US.…”
Section: Introductionmentioning
confidence: 96%